Difficulties That Lead to Conversion in Laparoscopic Cholecystectomy - Kamruzzaman, Md; Rahman, Md Shahidur; Khan, Abdul Kader; Afrin, Sadia (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Background: Cholelithiasis is one of the most common surgical problems throughout the world. Earlier, the prevailing treatment of symptomatic Cholelithiasis was an open cholecystectomy which is almost replaced by laparoscopic cholecystectomy. Although occasionaly switch to open cholecystectomy may require during the procedure which is known as conversion in laparoscopic cholecystectomy. Many factors contribute to the conversion which is not a sign of surgeon's failure rather is a sign of surgeon’s good surgical judgment. Our objectives are to find out the factors which are associated with conversion and thus reduce conversion rate, preoperative preparation and counseling the patient for conversion in laparoscopic cholecystectomy. Methods: This was a hospital based retrospective study, carried out in department of hepatobiliary & pancreatic surgery department, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from January 2008 to December 2009. A total no of 50 cases were included in our study which were converted to open cholecystectomy. Cases were collected from the hospital medical records which were retrieved and analyzed. Result: A total no of 768 laparoscopic cholecystectomies were attempted during the study period. Out of which 50 cases were converted to open cholecystectomy. Thus the conversion rate was 6.5%. Among these the reasons for conversion in both genders were dense adhesion in 22 (2.86%), aberrant anatomy in 10 (1.3%), empyema gall bladder in 4 (0.52%), per operative findings of choledocholithiasis in 3 (0.39%), suspicion of common bile duct injury in 3 (0.39%), others causes of conversion included uncontrolled bleeding 3 (0.39%), thick fibrosed gall bladder 2 (0.26%), accidental bowel injury 2 (0.26%), Type-I choledochal cyst 1 (0.13%) cases. Conclusion: various factors are related to conversion in laparoscopic cholecystectomy. But due to improvement of learning curve, good quality operative equipment, now a day’s laparoscopic cholecystectomy is safe method of treatment for gall stone diseases with very low conversion rate. J Bangladesh Coll Phys Surg 2024; 42: 235-240